Modelling value stream flows in the enterprise supply chain = Modelowanie przepływów strumieni wartości w łańcuchu dostaw przedsiębiorstwa - Kużdorowicz, Paweł; Witkowski, Krzysztof; Vidová, Helena (Zielona Góra: Faculty of Economics and Management Press)
Value stream flows in the supply chain This paper discusses supply chain management in an enterprise. A concept of modelling value stream flows defined in an integrated ERP-class information system is presented. The paper focuses on value stream flows in the areas of procurement, production, and sales in an enterprise. Such flows are illustrated by examples.
Keywords: łańcuch dostaw; model SCOR; strumień wartości; system ERP; supply chain; SCOR model; stream flow; ERP system